New Quinone Antibiotics against Methicillin-Resistant S. aureus - Javier Campanini-Salinas; Juan Andrades-Lagos; Nicolás Hinojosa; Fabián Moreno; Pedro Alarcón; Gerardo González-Rocha; Ian E. Burbulis; David Vásquez-Velásquez (MDPI AG, 2021)
There is an urgent need for the development of new antibiotics. Here, we describe the inhibitory activity of new quinone compounds against methicillin-resistant Staphylococcus aureus (ATCC® 43300), methicillin-sensitive S. aureus (ATCC® 29213), and two clinical isolates from Chile (ISP-213 and ISP-214). We observed 99.9% reduction in viability within 2 h of exposure without the cultures exhibiting any post-antibiotic effect, which was twice the kinetics to that observed with vancomycin. These clinical isolates did not acquire resistance to these quinone derivatives during the course of our study. We found that these compounds protected larvae of the greater wax moth, sp. Galleria mellonella, from infection by these MRSA clinical strains as effectively as vancomycin. These quinone derivatives are potential drug candidates worth further development.